2005
DOI: 10.4028/www.scientific.net/msf.475-479.2631
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Operational Conditions during Production of Lead-Calcium-Tin Anodes for Improve Their Mechanical Properties

Abstract: Previous works have shown that a minimum yield strength s0 of 58 MPa for leadcalcium- tin anodes of 6 mm thickness and a nominal composition of 0.7% Ca and 1.3% Sn are required to avoid early deformations and distortions during their operation in copper electrowinning cell. This s0 value for the anodes is associated with a terminal cold rolling process and a further precipitation hardening prior to their installation in the electrowinning cells. The objectives of the present work are to determine the alloy rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…without deformation hardening. 2 Figure 5 shows a typical optical micrograph of our anodes Figure 5a shows a recrystallised structure consistent with the annealing process, while in Fig. 5b, some deformed grain was observed.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…without deformation hardening. 2 Figure 5 shows a typical optical micrograph of our anodes Figure 5a shows a recrystallised structure consistent with the annealing process, while in Fig. 5b, some deformed grain was observed.…”
Section: Resultssupporting
confidence: 58%
“…The recrystallisation temperature of the anodes varies between 120 and 180uC according with Ca and Sn contents, being of 150uC for the nominal composition of 0?07%Ca and 1?3%Sn. 2 The hot rolling is done in three passes with an average strain rate of 2?5 s 21 and a total rolling time of 1-2 min, so no enough time is available for a complete recrystallisation and as a consequence some deformed grain appears, as shown in Fig. 5b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If this loss of thickness is combined with a low yield stress of the anodes, dependent on its precipitation and deformation hardening, these are much more likely to suffer premature deformations and distortions in cells, being not compatible for the optimal process due to over voltages, short circuits and other related problems which affect the cathodic copper quality. Regarding the yield stress of 6 mm thick anodes, Camurri et al [1][2][3][4][5] demonstrated that a minimum value of 58 MPa is needed to assure a working life of 4-5 years, if working at a typical current density of 300 A/m 2 . It was also demonstrated [1][2][3][4][5] that to achieve the appropriate minimum value of 58 MPa for the yield stress of aged anodes the contribution associated to the deformation hardening must be at least 20 MPa, reached with a 50% of area reduction during the final cold rolling process, from 12 to 6 mm of thickness.…”
Section: Introductionmentioning
confidence: 99%